Effect of solder material thickness on Power MOSFET reliability by Electro-thermo-Mechanical Simulations. (September 2018) - Cavallaro, D.; Greco, R.; Bazzano, G.
Abstract: Electro-thermal-mechanical simulation by Finite Element Model (FEM) has been employed in fatigue analysis of a MOSFET structure under electro-thermal stress. The purpose of the simulation activity is to estimate the impact of solder layer thickness and thickness uniformity on power device reliability under passive and active tests. Thermal and power cycles have been simulated and stress, strain, and number of cycles to failure have been evaluated using FEM. It has been observed that thermal cycling to the point of maximum stress in the solder layer occurs at the edge of the die and that, according to a strain based Coffin-Manson fatigue model, increased thickness correlates to a gain in the number of cycles to failure, that is, until a thickness limit is reached. In power cycling the most stressed material is the top metallization since the heat flow does not involve the die-attach, so the Bonding Line Thickness (BLT) increasing does not produce any temperature variation at top metal level. Highlights: Increasing solder thickness in Power device produces a gain in lifetime. A limit value in solder thickness is reached beyond which no benefit is obtained. Thickness non-uniformity of solder implies a larger fatigue in thermal stress. The minimum thickness of the solder is critical in thermal cycling. Maximum stress in the solder layer is at the corner and side edge of the layer.